"Usage of Silver-Stained Polyacrylamide Gels Electrophoresis (PAGE) for Detection of Rotavirus Infection by Direct Identification of Viral Nucleic Acid ." (KYAMC Journal, 2017)
Background: Rotavirus infects almost all children by the age of five. More than 180,000 annual deaths due to rotavirus, occurs in Bangladesh.Aims: This study aimed to determine the incidence of rotavirus infection in children by a modified polyacrylamide gel elctrophoretic (PAGE) in stool samples.Materials and Methods: In this descriptive type cross sectional study, a total of 400 stool samples were examined for the presence of rotavirus by a modified PAGE analysis of viral genome. Stool culture was done for common enteric pathogens. The study was carried out from November 2012 to July 2013 in the department of Microbiology, Mymensingh Medical College, Mymensingh.Results: PAGE results were found in 365 of 400 (91%) specimens. Maximum incidence of rotavirus infection was seen in age group of 6 months - 24 months (67.25%). All 151 rotavirus positive cases did not show infection with bacterial pathogens.Conclusion: The modified PAGE technique for the detection of viral RNA was found to be rapid, simple, reliable and less expensive technique.KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 557-561